Fractalkine is an independent predictor of mortality in patients with advanced heart failure - Richter, Bernhard; Koller, Lorenz; Hohensinner, Philipp J.; Rychli, Kathrin; Zorn, Gerlinde; Goliasch, Georg; Berger, Rudolf; Mörtl, Deddo; Maurer, Gerald; Huber, Kurt; Pacher, Richard; Wojta, Johann; Hülsmann, Martin; Niessner, Alexander (Thrombosis and Haemostasis, 2012)
Immunological processes are implicated in the multifactorial pathophysiology of heart failure (HF). The multifunctional chemokine fractalkine (CX3CL1) promotes the extravasation of cytotoxic lymphocytes into tissues. We aimed to assess the prognostic value of fractalkine in HF. Fractalkine plasma levels were determined in 349 patients with advanced systolic HF (median 75 years, 66% male). During a median follow-up of 4.9 years (interquartile range: 4.6–5.2), 55.9% of patients died. Fractalkine was a significant predictor of all-cause mortality (p <0.001) with a hazard ratio of 2.78 (95% confidence interval: 1.95–3.95) for the third compared to the first tertile. This association remained significant after multivariable adjustment for demographics, clinical predictive variables and N-terminal pro-B-type natriuretic peptide (NT-proBNP, p=0.008). The predictive value of fractalkine did not significantly differ between patients with ischaemic and non-ischaemic HF aetiology (p=0.79). The predictive value of fractalkine tertiles was not significantly modified by tertiles of NT-proBNP (p=0.18) but was more pronounced in the first and third tertile of NT-proBNP. Fractalkine was also an independent predictor of cardiovascular mortality (p=0.015). Fractalkine levels were significantly lower in patients on angiotensin-converting enzyme inhibitor therapy (p <0.001). In conclusion, circulating fractalkine with its pro-inflammatory and immunomodulatory effects is an independent predictor of mortality in advanced HF patients. Fractalkine improves risk prediction beyond NTproBNP and might therefore help to identify high risk patients who need special care. Our data indicate the implication of immune modulation in HF pathology.
Keywords: Fractalkine; chemokine; heart failure; immunology; prognosis